Analisis dan Evaluasi Pelaksanaan Program Komunitas Belajar di SMA Negeri 1 Teluk Gelam - Zwesty Wulandari; Elsha Vitria Fitriani; Darmawi Husni (CV. Ulil Albab Corp, 2026)
This study aims to describe and analyze the implementation of the Learning Community program at SMA Negeri 1 Teluk Gelam as a strategy to enhance teacher professional development within the context of an autonomous curriculum. This research employed a qualitative approach with an in-depth single case study design. Data collection was conducted through in-depth interviews, observations, and document review. The data were then analyzed using the Miles, Huberman, and Saldana model, which includes data condensation, presentation, and drawing and verifying conclusions. The research findings indicate that the program design aligns with the principles of Professional Learning Communities (PLCs), such as collaboration, group work, and an orientation toward improving student learning outcomes. Program implementation was fairly consistent through regular meetings, learning activities, and sessions sharing effective teaching practices. However, several challenges were encountered, including time constraints, varying teacher commitment, and inadequate technical support. The program had a positive impact on improving teachers' pedagogical and professional competencies, particularly in developing lesson plans, implementing innovative methods, and strengthening a collaborative culture. This study confirms that Learning Communities can be an effective means of improving teacher competency, provided they are supported by strong school leadership, adequate time, and ongoing evaluation mechanisms.